The value of non-native fish species : a study of recreational angling in the Amathole district - Kinghorn, James Wolmarans (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2013)
Experience has shown that effective fisheries governance requires a sound understanding of fisheries as systems incorporating both ecological and human dimensions. The Ecosystem Approach to Fisheries requires that the human components of these systems be considered when developing management and governance frameworks. While the potential for inland fisheries to contribute towards societal welfare and the development of rural livelihoods is becoming increasingly apparent, developing South African inland fisheries requires a careful consideration of both their positive and negative impacts, given that they revolve mainly around five of the world"Ÿs top 100 invasive species. This thesis aimed to explore the value of inland recreational fisheries to rural livelihoods in the Amathole District of South Africa, to the regional economy, and to anglers themselves. Three methods were used to isolate this value. Economic impact analysis was used to estimate the combined total economic impact of the 2011 Divisional Tournament (n=31) and the 2012 Amatola Bass Classic (n=100) on the regional economy of the Amathole District, estimated to be R106 625. The travel cost method was applied to data from the 2012 Amatola Bass Classic in order to estimate the social welfare generated by this tournament. The Negative Binomial model, corrected for truncation and endogenous stratification, estimated this value at R 1 960 090. The sustainable livelihoods framework was used to conduct a broad-based analysis of the value of Amatola Wild Trout, the firm which constitutes the fishery surrounding the rural village of Cata. It was found that the fishery had been responsible for a modest pecuniary impact on the community of Cata within its first two years of establishment, although significant improvements in human capital were found to have resulted from the development of the fishery. These results provide insights into the economic dimension of fisheries in the Amathole District, and will prove useful when weighing up the positive and negative impacts of non-native fish species, particularly when informing decisions regarding their potential eradication.
Keywords: Fishing -- Economic aspects -- South Africa -- Eastern Cape Introduced fishes -- Economic aspects -- South Africa -- Eastern Cape Fisheries -- South Africa -- Eastern Cape; Non-native fish species; Recreational angling; Amathole district